Os conceitos hegelianos de Lüge (mentira), Täuschung (ilusão ou engano) e Betrug (fraude ou impostura) (Revista Eletrônica Estudos Hegelianos, 2017)
ABSTRACT: The purpose of this paper is to present and analyze the Hegelian concepts of lie (Lüge), illusion or deceit (Täuschung) and fraud or imposture (Betrug), that are essential to the understanding of Hegel’s Philosophy of Law or Political Philosophy. In short, the verbs to lie (lügen) and to elude or deceive (täuschen - betrügen) are strictly used in Hegel to clarify, for example, the question of the supposed ‘duty to tell the truth’ (Pflicht die Wahrheit zu sagen), according to Kant. To this end, we base our analysis on Hegel’s classical texts as well as on other specific works on the concepts mentioned above.